Increased abundance of bacteria of the family Muribaculaceae achieved by fecal microbiome transplantation correlates with the inhibition of kidney calcium oxalate stone deposition in experimental rats - Wang, Yan; Sun, JinBo; Xie, Sen; Zhou, Yu; Wang, Tao; Liu, ZhenYu; Li, ChaoSheng; Gao, Lei; Pan, TieJun (Frontiers in Cellular and Infection Microbiology, 2023)
Background The incidence of nephrolithiasis is increasing rapidly worldwide. Calcium oxalate is the most common constituent, contributing to approximately 80% of all kidney stones. The gut microbiome, through its oxalate-degrading ability, may play a role in decreasing morbidity due to urinary calculus. Fecal microbiome transplantation (FMT) has been reported to be effective in restoring the gastrointestinal microbial community in different conditions. The transplantation of whole communities that have oxalate-degrading function may be a more effective strategy than the transplantation of isolated strains. Methods FMT was carried out in male guinea pigs and male Sprague–Dawley laboratory rats (SDRs). Fresh feces were collected from guinea pigs housed in metabolic cages. SDRs were divided into four groups: two groups received standard rat chow (SC) (groups SC and SC + FMT), and two groups were fed a 5% potassium oxalate diet (OD) (groups OD + phosphate-buffered saline (PBS) and OD + FMT). On day 14, groups OD + PBS, OD + FMT, and SC + FMT received either PBS or guinea pig feces by esophageal gavage. The composition of the microbiota of guinea pigs and SDRs was analyzed using a 16S rRNA gene sequencing approach. Biochemical analysis of urine samples from SDRs revealed the presence of calcium oxalate (CaOx) crystals, which were presumed to originate from kidney stones. Renal function was examined using real-time PCR analysis and immunohistochemical staining for renin, angiotensin-converting enzyme, and osteopontin (OPN) expression. Results FMT resulted in a gut microbiota that was a mixture of guinea pig and SDR bacteria. A microbial network involving Muribaculaceae, Lactobacillus, and Bifidobacterium was activated by FMT in group OD + FMT. As a result, urinary oxalate, calcium, uric acid, creatinine and urea in urine samples were reduced significantly. Similarly, significant reduction of uric acid and blood urea nitrogen to creatinine ratio in serum samples was observed (p < 0.05). Microscopic observations revealed a high CaOx crystal score (4+) in the kidneys of rats in group OD + PBS, whereas a lower score (2+) was observed in the rats in group OD + FMT. Up-regulation of OPN and down-regulation of renin were also associated with FMT. Conclusion A microbial network involving Muribaculaceae and other oxalate-degrading bacteria achieved by FMT was capable of reducing urinary oxalate excretion and CaOx crystal deposition in the kidney through increasing intestinal oxalate degradation. FMT may exert a renoprotective function in oxalate-related kidney stones.